2013
DOI: 10.1161/hypertensionaha.111.01030
|View full text |Cite
|
Sign up to set email alerts
|

High Intake of Dietary Long-Chain ω-3 Fatty Acids Is Associated With Lower Blood Pressure in Children Born With Low Birth Weight

Abstract: Reduced fetal growth is associated with increased systolic blood pressure. Recently, we found an inverse association between serum ω-3 fatty acids and systolic blood pressure in young adults born with impaired fetal growth. We investigated the associations of dietary intake in childhood of the long-chain ω-3 fatty acids eicosapentaenoic acid and docosahexaenoic acid with blood pressure parameters in children born with reduced birth weight. We analyzed data from 3457 children aged 8 to 15 years participating in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 26 publications
2
31
1
1
Order By: Relevance
“…Large population studies seem to confirm a significant inverse correlation between low birth weight and blood pressure in people of all ages. [27][28][29] However, the fact that this association has been reported to be of little magnitude (an increase of 1-4 mm Hg) could explain the nonsignificant results of the present study and other previous reports with relatively low sample sizes. 12,30 Regarding vascular wall thickness, there is no data from large population studies, but recent cohort studies have reported normal 31 or increased IMT 32 in adolescents and young adults with FGR.…”
contrasting
confidence: 51%
See 1 more Smart Citation
“…Large population studies seem to confirm a significant inverse correlation between low birth weight and blood pressure in people of all ages. [27][28][29] However, the fact that this association has been reported to be of little magnitude (an increase of 1-4 mm Hg) could explain the nonsignificant results of the present study and other previous reports with relatively low sample sizes. 12,30 Regarding vascular wall thickness, there is no data from large population studies, but recent cohort studies have reported normal 31 or increased IMT 32 in adolescents and young adults with FGR.…”
contrasting
confidence: 51%
“…Although most studies agree that blood pressure and IMT are consistently increased in neonates and children with FGR, 3,26,27 literature on vascular structure and function in FGR adolescents and young adults is controversial. Large population studies seem to confirm a significant inverse correlation between low birth weight and blood pressure in people of all ages.…”
mentioning
confidence: 99%
“…The effects of functional foods for CAD risk reduction in a meta-analysis showed that these foods are protective against CAD [34].In another systematic review of studies, which included the results from 14 human studies (7 prospective, 3 cross-sectional, 1 controlled, 3 case-control) and 13 animal studies, found that dietary omega-6 to omega-3 fatty acid ratio can influence brain composition [35], Alzheimer's disease pathology, and behavior (as according to animal studies), and revealed an association between the omega-6 to omega-3 ratio, cognitive decline, and incidence of dementia. This review supports growing evidence of a positive association high intake of dietary long-chain ω-3 fatty acids was associated with lower blood pressure in children born with low birth weight [36].…”
Section: Clinical Evidence On Diet and Ncdssupporting
confidence: 82%
“…Data from the generation R study suggest that macronutrient intake is not consistently associated to BP in childhood. On the contrary, the NHANES survey showed a protective effect of high dietary intakes of eicosapentaenoic acid and docosahexaenoic acid on SBP only among those children with low birth weight (37). This discordance may be explained by differences in the study populations and the type of nutritional questionnaires used in the studies.…”
Section: Discussionmentioning
confidence: 92%